Care pathways for people with major depressive disorder - Strawbridge, Rebecca (2022)
Funding: This work was supported by the European Brain Council (EBC). This work is also supported by the National Institute for Health Research (NIHR) Maudsley Biomedical Research Centre at South London and Maudsley NHS Foundation Trust and King’s College London.